1998
DOI: 10.1080/00224549809600406
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Handicapping Tendencies

Abstract: This study was undertaken to determine when U.S. children begin to self-handicap, that is, to reduce preparation effort before evaluations rather than applying themselves to do their best. The personal variables examined for their impact on practice behavior were gender, grade level, and self-esteem. The situational variables were time of the self-esteem test (before or after the evaluation task) and importance of the evaluation task. The results showed that (a) the 6th-grade boys were more likely than the 6th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…Previous research reported differences between females and males in terms of self-handicapping (e.g., Kimble et al, 1998;Rhodewalt & Davison, 1986). Therefore, preliminary analysis was conducted for gender on the SHS scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research reported differences between females and males in terms of self-handicapping (e.g., Kimble et al, 1998;Rhodewalt & Davison, 1986). Therefore, preliminary analysis was conducted for gender on the SHS scores.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that female students had higher self-handicapping scores when compared to male students. The literature on self-handicapping includes many studies that find men resorting to self-handicapping strategies more often than women (e.g., Kimble et al, 1998;Rhodewalt & Davison, 1986). Some other authors have reported that self-handicapping does not differ depending on gender (e. g., Leondari & Gonida, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a picturematching task that has been used in past research on selfhandicapping in children (Kimble et al, 1998). Each problem on the picture-matching task consisted of a series of four abstract figures, followed by a blank space.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, then, self-handicapping helps guard against the potentially harmful effects of failure on self-esteem. Research supports self-handicapping theory for both adults (e.g., McCrae & Hirt, 2001) and children (Kimble, Kimble, & Croy, 1998;Ryska, 2002).…”
mentioning
confidence: 86%